Let's Get Serious: Communicating Commitment In Romantic Relationships - ACKERMAN, J. M. (Institutional Knowledge at Singapore Management University, 2010)
Are men or women more likely to confess love first in romantic relationships? Who is more likely to respond happily? An evolutionary-economics perspective contends that women and men incur different potential costs and benefits from confessing love and from reacting positively to such confessions. Across four studies, we find that although people believe that women are the first to confess love and feel happier upon receiving confessions, it is actually men who confess love first and feel happier. Reactions also differ drastically depending on whether the couple has or has not engaged in sexual activity, as well as the mating strategy a person is pursuing. Thus, saying and hearing ―I love you‖ has different meanings depending on who is doing the confessing and when those confessions are made. An evolutionary-economics perspective further suggests that displays of non-romantic commitment, and reactions to these displays, will be influenced by specific, functional biases.